A Descent Modification of Conjugate Gradient Method for Optimization Models - Sulaiman, Ibrahim Mohammed; Mamat, Mustafa; Kamfa, Kamilu; Danlami, Muktar (Iraqi Journal of Science, 2020)
In this paper, we suggest a descent modification of the conjugate gradient method which converges globally provided that the exact minimization condition is satisfied. Preliminary numerical experiments on some benchmark problems show that the method is efficient and promising.